Validitas Konstruk Alat Tes Nijmeegse Schoolbekwaamheids Test - Medianta Tarigan; Fadillah (Journal of Research and Measurement in Psychology: JPPP, 2022)
This study aims is to provide construct validity information about the psychometric properties of the Nijmeegse Schoolbekwaamheids Test (NST). NST is one of the instruments that is widely used to measure school readiness. The NST has 10 subtests in the form of pictures and stories that were adapted from the Netherlands. This study involved 471 pre-school students aged 4-6 years. This study used IRT to determine the quality of each item, Exploratory Factor Analysis to determine the new factors formed from the 10 available subtests, and Confirmatory Factor Analysis to determine to construct validity. The IRT 3PL model showed that all items in the NST are valid, but it is necessary to review several items, especially in subtest 10. In the EFA factor analysis, 4 new factors were found that measure the level of factor: logic reasoning ability, memory, fine motor skill, and conceptual maturity in children. These are valid and reliable as evidenced by the RMSEA value on the CFA of 0.05 and the reliability value of 0.87.